Literasi Keuangan Mahasiswa Kampus Ciputra Makassar - Zarkasih, Mario; Wiyarta, Ferrel Hansel; Mustikarini, Carolina (Jurnal Online Manajemen ELPEI, 2025)
Research from around the world has proven that financial literacy is lower, particularly among the youth, which causes serious problems about individuals' ability to secure their financial well-being. Changing circumstances drive the changing needs of individuals, along with the dynamic nature of financial products. Therefore, this research aims to examine financial literacy among young people, particularly university students at Ciputra University Makassar. This research is quantitative. The population in this study is Ciputra University Makassar students. The sample used in this study consists of 51 students from Ciputra University Makassar. The sampling technique uses a questionnaire. This research collects primary data by distributing questionnaires to Ciputra University Makassar students. The method used in this study is the Partial Least Square (PLS) method with SmartPLS 3.0 software. Based on the research results, it can be concluded that financial awareness has a significant impact on financial skills. Financial awareness has a significant effect on financial capability, while financial skills do not significantly affect financial capability.